Global Trend of Factors and Effective Learning in Renewable Energy Education: A Systematic Literature Review - Santika, Yuriz Ananda; Jamaluddin, Anif; Sukarmin, S (Universitas Muhammadiyah Surakarta, 2024)
The current study is a systematic review of success factors in renewable energy learning and effective learning systems in teaching renewable energy topics and analyzing trends in renewable energy topics globally. Eighty-five articles from 2014 to 2024 have been analyzed to compile a comprehensive picture of the latest developments and challenges in renewable energy education. The results show that the use of technologies such as Virtual Reality (VR) and virtual laboratories, as well as the integration of hands-on projects such as solar panel manufacturing programs, positively impact students' understanding and skills. Collaboration between industry and academia, along with active learning approaches such as Problem-based learning (PBL), Project-based Learning (PjBL), and Science, Technology, Engineering, Arts, and Mathematics (STEAM), proved effective in improving student learning outcomes, motivation, and participation. The findings highlight the enhanced interest and focus on renewable energy at the global level. The implications of this research emphasize the importance of encouraging the development of innovative and relevant learning designs to support the transition to an energy-sustainable future. By understanding success factors and effective learning strategies, educational institutions could be better equipped to meet the demands of a skilled renewable energy workforce and help accelerate the adoption of green technologies and practices in a globalized society.